The Management Accountant in Budgetary Process Values Inclination, Employees’ Motivation and Productivity: A Tropical Nation in Contextual View - Umo, Usen Paul (Current Topics on Business, Economics and Finance Vol. 4, 2023)
The management accountant occupies a position which makes him a conspicuous personnel in the management system of firms. If there is anything that makes his presence felt in an organizational setting, it is the budget. His values inclination and preferred style of leadership (authoritarian or humanistic) will determine to a large extent the nature of budget prepared in business organizations. Employees will usually react negatively to the authoritarian management accountant’s budgets but organizational effectiveness and efficiency are often the results of budgets prepared in firms which the management accountant is humanistic (democratic). While conceding the fact that certain business settings may require a certain degree of authoritarian budgetary process, this work submits inter-alia: Many accounting literature and empirical evidence are in support of the fact that in a majority of cases, the humanistic approach to budget formation produces better results as far as effectiveness and efficiency of organizations are concerned. In total, the unconcerned attitude of management accountants towards current researches in budgetary science (theory and practice), values inclination in budgetary practice, the falling standard in work morale and motivation, declining productivity trend in firms, the magnitude of corruption in the business world and society generally and the economic depression developing economies (such as Nigeria) is facing today have raised tremendous concern. Strategies must be evolved, values inclination must be harnessed, secured and must also be humanistic, work morale and motivation must be heightened, budget acceptance must be secured, goals stream must be strengthened, interpersonal trust and shared feeling of confidence must be recovered in the budgetary system of firms and improved productivity must be targeted. Admittedly, real participation in budgetary process is a panacea. Its benefits do not automatically arise from the budgetary process. They must be worked for. The humanistic management accountant can do this. The participation, and not the least, the commitment of all levels of the organization in budgetary process will make the budget real and accepted.